Oral appliances therapy for sleep disorders - Piorunek, Tomasz; Cofta, Szczepan; Rzymkowska, Małgorzata (Przewodnik Lekarza/Guide for GPs, 2010)
Treatment sleep apnea disirders with oral appliances (OA) can be alternative to continuous positive airway pressure (CPAP). These devices produce enlargement of the upper airway by advancing the mandible, tongue and other structures in oral cavity. Oral appliances effectively reduce snoring and sleep disorders in mild obstructive sleep apnea. There are two main types of oral appliances. Mandibular repositioning appliances (MRA) advancing the mandible and/or tongue, tongue retaining devices (TRD) draws and holds the tongue in an anterior position. Oral appliances cause short-term and long-term adverse effects in some of patients.